PAX 4 GENE MUTATION IN A 9-YEAROLD CHINESE BOY PRESENTING WITH DIABETIC KETOSIS - Lee, Yee Lin; Muhamad, Siti Nur Aina binti; Ting, Tzer Hwu (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION A 9-year-old Chinese boy presented with diabetic ketosis following one month history of polyuria, polydipsia and nocturnal enuresis. A strong family history of diabetes was present within his family pedigree whereby both his mother and maternal grandmother were diagnosed with type 2 diabetes at 15 years and 28 years old respectively. His 10-year old sister was also recently diagnosed with impaired glucose tolerance. The patient’s body mass index (BMI) was normal at the 75th centile and there was absence of acanthosis nigricans. Anti-glutamic acid decarboxylase (GAD) and anti-islet tyrosine phosphatase 2 (IA2) were negative but anti-islet cell (ICA) was weakly positive. The patient was treated as type 1 diabetes with subcutaneous insulin therapy. Insulin treatment was withheld 1 month post diagnosis due to frequent hypoglycemia but subsequently restarted after 5 months post diagnosis, with gradual dose increment. The patient was able to maintain good glycemic control with insulin total daily dose of less than 0.5U/kg/day, alluding to the diagnosis of honeymoon period. The patient underwent genetic testing for MODY and was found to carry a heterozygous mutation of PAX4 gene, Exon 9, c.890G>A (p.Gly297Asp) of uncertain significance. CONCLUSION PAX4 mutation is a rare cause of MODY, initially reported in Thai patients. PAX4 mutations are associated with younger onset of type 2 diabetes, particularly in East Asians/Chinese. It is unclear if this child has type 1 DM or MODY due to PAX4 mutation. Further genetic testing of his family members is needed to determine the significance of this PAX4 variant and association with young onset diabetes. A more protracted follow up is needed to unveil this patient’s diabetes progression and phenotype.